Correction to the scientific name of two recently described Brazilian species of crickets (Grylloidea: Phalangopsidae) - Costa, Henrique C. (Zootaxa, 2012)
In a work published little over two years ago, Mews et al. (2009) described some new taxa of Brazilian phalangopsid crickets. Two specific names, however, were incorrectly formed under the articles of the International Code of Zoological Nomenclature (ICZN 1999), leading to the need of justified emendations, according to Article 33.2.2 of the Code (ICZN 1999), which I will give below.